EXPLORING THE EFFECT OF CHEMLAB SOFTWARE IN CHEMISTRY EDUCATION IN SECONDARY SCHOOLS IN ANAMBRA STATE, NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This study investigates the impact of Chemlab software on chemistry education among secondary school students in Anambra State, Nigeria. Utilizing a quasi-experimental design, the research examines how this virtual laboratory tool influences students’ academic achievement, engagement, and practical skills in chemistry. The findings indicate that Chemlab software significantly enhances students’ understanding of chemical concepts, improves retention, and fosters a positive attitude toward practical chemistry. Gender differences were also explored, revealing no significant variation in outcomes. The study underscores the potential of virtual laboratory tools to address infrastructural challenges in Nigerian secondary schools, offering practical implications for educators and policymakers aiming to improve science education.